Poverty, health, and ecosystems : experience from Asia. Chapter 3, Poverty, health and ecosystems - Cenzano, Romina (2014)
TÍTULO DEL TEXTO O TEXTOS SELECCIONADOS PARA TRADUCCIÓN: Poverty, Health, and Ecosystems: Experience from Asia Nota: Traducir capítulo 3: “POVERTY, HEALTH AND ECOSYSTEMS” páginas 95 a 116 hasta llegar a “Discussion and Summary of Main Findings”. FUENTE: Steele, P, G. Oviedo, and D.McCauley (Eds.) 2006. Poverty, Health, and Ecosystems: Experience from Asia, IUCN, Gland, Switzerland and Cambridge, UK and Asian Development Bank, Manila, Philippines